Experimental study on saturation pool boiling heat transfer characteristics of R245fa on the surface covered by sintered copper powder. (September 2022) - Dang, Chao; Pan, Lingyun; Min, Ruiqi; Yin, Liaofei; Ding, Yi; Jia, Hongwei
Abstract: In this paper, the mechanism of pool boiling heat transfer enhancement on the surface covered with sintered copper powder porous layer has been investigated. The refrigerant R245fa with great application prospect in electronic cooling field was selected as the test fluid. According to the results, the boiling heat transfer performance of R245fa could be effectively enhanced by attaching the sintered copper powder porous layer to the plain copper surface. Even when the wall superheat was as low as 2.2 °C, the sintered copper powder surface with the particle size of 110 μm and thickness of 0.6 mm could still be efficiently triggered to boiling. The heat transfer coefficient and CHF were significantly improved up to 247.71% and 255.15% compared with that of plain copper surface, respectively. However, with the thickness of porous layer increased from 0.6 mm to 0.9 mm, the maximum heat transfer coefficient for the enhanced surface with particle size of 30 μm went up to 136.01%, while the CHF value decreased by 92.52%. For 65 μm and 110 μm surfaces, the change of porous layer thickness had little effect on the heat transfer coefficient in the initial boiling stage, but presented the contrary influence trend at high heat flux conditions.